Kineticstudy, surface characterization, and corrosion inhibition of mild steel in acidic media using septrin and flagyl - Benjamin Ufuoma Oreko, Samuel Batet, Okuma Silas Oseme. (Zastita Materijala, 2026)
Over the years, there has been increasing interest in the use of pharmaceutical compounds as corrosion inhibitors owing to their eco-friendly nature and their high efficiency in inhibiting corrosion in metallic materials. The corrosion inhibition effectiveness of the two drugs, septrin and flagyl, on mild steel in a 2MHCl solution at 30°C for different exposure times of 48, 96, 144, 192, and 240 hrs is studied. In the research work, the main objectives focused on adsorption behavior and the kinetics process. The weight-loss method showed that Septrin had an inhibition efficiency (IE) value of 97.7%, and Flagyl had an IE value of 76.7%. This means that both of them were effective at reducing corrosion in the acidic medium. The isothermal models, the free energy of adsorption values, suggest physisorption for both drugs and show the nature of the interaction between the inhibitor molecules and the metal surface. Kinetic studies further indicated that mild steel exhibits a longer half-life in the presence of septrin compared to flagyl, suggesting superior protection. Also, the scanning electron microscopy (SEM) analysis confirmed the presence of a protective filmon the steel surface, which averted further corrosion on the steel. This research highlights the promising use of Septrin and Flagyl as corrosion inhibitors for mild steel in acidic conditions
Gravimetric Analysis ,Surface Characterization, Adsorption Study of Septrin and Flagyl in 2 mol/l concentration of HCL.
Keywords: Gravimetric Technique; Inhibition efficiency; inhibitory drugs; physisorption mechanism; Adsorption mechanism; Protective film; Dissolution